Size Effect on Stock Returns based on Asset Pricing Models in Chinese Stock Market - Yin, Shiyan (2018)
This dissertation aims to examine the size effect pattern on stock returns based on asset pricing models in China’s stock market. Empirical tests were carried out according to traditional and modified Fama French three-factor models and characteristic-based model. Unlike several research papers, which have shown that firm size effect is linear, I found an inverted-U shape in the firm scale effect on stock return in China by investigating samples selected from A-shares on the Shanghai and Shenzhen Exchange Market in the period between 2010 and 2017. At the lower level of firm size, it has positive influence on stock returns; however, high levels of firm scale have negative influence on stock returns.